2018
DOI: 10.1051/0004-6361/201732335
|View full text |Cite
|
Sign up to set email alerts
|

The WISSH quasars project

Abstract: Winds accelerated by active galactic nuclei (AGNs) are invoked in the most successful models of galaxy evolution to explain the observed physical and evolutionary properties of massive galaxies. Winds are expected to deposit energy and momentum into the interstellar medium (ISM), thus regulating both star formation and supermassive black hole (SMBH) growth. We undertook a multiband observing program aimed at obtaining a complete census of winds in a sample of WISE/SDSS selected hyper-luminous (WISSH) quasars (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
160
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(191 citation statements)
references
References 106 publications
25
160
1
Order By: Relevance
“…3.1). Our measured velocity offset of the C IV line (−5097 km s −1 ) is consistent, within the errors, with the value reported in Table 6 of Vietri et al (2018) for the source (−4670 km s −1 ). Such sources may point to additional spectral parameters that should be taken into account in future prescriptions for UV-based redshift corrections.…”
Section: Sdss Pipesupporting
confidence: 90%
“…3.1). Our measured velocity offset of the C IV line (−5097 km s −1 ) is consistent, within the errors, with the value reported in Table 6 of Vietri et al (2018) for the source (−4670 km s −1 ). Such sources may point to additional spectral parameters that should be taken into account in future prescriptions for UV-based redshift corrections.…”
Section: Sdss Pipesupporting
confidence: 90%
“…A quasars -suggests that a virialized sub-system emitting mainly LILs coexists with outflowing gas. Even at the highest luminosity the data (Sulentic et al, 2017;Vietri et al, 2018;Coatman et al, 2016) remain consistent with a scenario that posits a dichotomy within the BLR, where the blue shifted emission is produced in clumps of gas or a continuous wind (Collin-Souffrin et al, 1988;Elvis, 2000), and LILs are emitted by gas in virial motion. In this scenario, we observe a net blueshift in CIVλ1549 because of the large gas velocity field component along the radial direction, with the receding side of the flow obscured by an optically thick equatorial structure, most likely associated with the accretion disk.…”
Section: A Main Sequence For Type-1 (Unobscured) Quasarssupporting
confidence: 75%
“…The comparison between LILs and HILs has provided insightful constraints of the BLR at low-z (Marziani et al, 1996), and this is even more true if the comparison of Hβ and CIVλ1549 is carried out at high L (Sulentic et al, 2017;Bisogni et al, 2017;Shen, 2016;Vietri et al, 2018). Perhaps the most remarkable fact is that a LIL-BLR appears to remain basically virialized (Marziani et al, 2009;Sulentic et al, 2017).…”
Section: A Main Sequence For Type-1 (Unobscured) Quasarsmentioning
confidence: 99%
“…Many authors have found a correlation (although with a huge scatter) between the bolometric correction and either the Eddington ratio (λ EDD = L bol /L EDD ) or the BH mass (e.g., Vasudevan & Fabian 2007;Vasudevan et al 2009;Lusso et al 2010). We studied these dependencies using the same samples presented above, but limited only to the 745 objects for which the M BH has been measured: 21 type 1 and 15 type 2 sources by Onori et al (2017b) for the SWIFT/BAT sample (which M BH has been derived from reverberation mapping techniques and deep NIR spectroscopy, see Section 2); 11 WISSH type 1 sources (with Hβ-based virial masses provided in Vietri et al 2018); 661 COSMOS AGN by L12 (with masses obtained from virial estimators for the type 1 AGN and from M BH -M * relations plus morphological information for the type 2 sub-sample); and the 37 XXL sources (which have virial masses estimated from Hβ, Mg II and C IV broad lines). To have measurements as homogeneous as possible, we re-scaled the BH mass values of the SWIFT sample by assuming the same virial factor (f=5.5) as the other samples (rather than f=4.31 as in Ricci et al 2017c).…”
Section: Bolometric Correction As a Function Of Eddington Ratio And Bmentioning
confidence: 99%